KEBIJAKAN KEPALA SMP NEGERI 1 AIMAS DALAM IMPLEMENTASI MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH (MPMBS) - Wisnu Wardoyo; Rustamadji (CV. ADIBA AISHA AMIRA, 2024)
This study assessed the principal's competence in implementing School-Based Quality Improvement Management (Manajemen Peningkatan Mutu Berbasis Sekolah, or MPMBS) using qualitative methods, focusing on the MPMBS Program's execution. Participants included the principal, vice principal, teachers, administrative staff, students, and the school committee. Data were gathered through interviews, documentation, and observation. The principal's implementation of MPMBS comprised several aspects: 1.) ensuring the teaching and learning process meets customer satisfaction, 2.) planning school programs to align with cultural demands and student needs, 3.) managing the curriculum through planning, organizing, implementing, and evaluating, 4.) handling human resources by developing, compensating, and motivating personnel, 5.) managing equipment and supplies to provide optimal learning facilities, 6.) overseeing finances transparently, 7.) delivering student services from entry to exit, 8.) fostering school-community relations through cooperation, and 9.) managing the school climate to create a conducive environment. Recommendations suggest the Sorong Regency Education and Culture Office should further encourage schools to empower the implementation of School-Based Quality Improvement Management.